Improving the Ability to Recognize Alphabet Letters Through the Use of Educational Posters on Alphabet Sounds for Mildly Mentally Impaired Children - Fauziyah Tabitha Wandari; Damri Damri; Asep Ahmad Sopandi; Grahita Kusumastuti (Edumaspul: Jurnal Pendidikan, 2024)
This research focuses on improving the ability to recognize alphabet letters in mildly mentally retarded children at SLB Negeri 1 Harau, Limapuluh Kota Regency by using educational posters for alphabet sounds. Alphabet sound education poster media can combine audio and visual functions by pressing the buttons available on the media. This research uses a quantitative approach with experimental methods, namely Single Subject Research (SSR) and A1-B-A2 Design, and data is analyzed using visual graphs by entering data in graphs which are then analyzed based on conditions A1-B-A2. The results of research using educational posters using alphabet sound media can improve the ability to recognize alphabet letters in mildly mentally retarded children at SLB Negeri 1 Harau, Kabupaten Lima Puluh Kota.